Studies on Incidence, Clinical Features and Ultrasonographic Changes in Urinary Tract Infections of Dogs in and around Navsari, Gujarat - Patel, Dharmi G; Patel, Manish D; Mehta, Sudhir A; Parmar, Saurabh M; Vala, Jignesh A (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Considering urinary tract infections as commonly encountered ailment in dogs and cats which accounts for significant use of  antimicrobials, the present study was carried out to know the incidence and clinical features of urinary tract infection (UTI) in dogs in  and around Navsari. During study period, 37 of 895 registered cases were primarily suspected for UTI based on clinical sings. Of which,  18 dogs were found positive for pyuria/bacteria on microscopic examination of urine with 2.0% (18/895) overall incidence. The hospital  based incidence among the suspected cases was 48.64% (18/37). Significantly, higher incidence was observed in dogs aged between 6-10  years (50.0 %) followed by 2.5-6.0 year (44.45%) and the least in > 10 year (5.55%) age group. The incidence was comparatively higher  in males (61.1%) than in females (38.9%). Breed-wise, the higher incidence of UTI was observed in Labrador Retriever (27.8%) followed  by non-descript, Pug, German Shepherd, Cocker Spaniel and crossbreds (11.1% each) and Pomeranian, Doberman and Saint Bernard  contributed 5.60% each. Clinical signs included inappetance (77.80%), haematuria (61.11%) and dribbling of urine along with stranguria  (38.90%). Additional signs were pale/anaemic mucous membranes and dullness/depression (27.80%), pyrexia (22.20%), dysuria (16.70%)  and vomiting (11.10%). Vital parameters showed non-significant difference from healthy dogs. About 50% dogs had K/Ao ratio within  normal range, whereas, 16.67% cases showed enlarged kidneys. Most dogs had normal echogenicity and normal cortico-medullary  distinction. Urinary bladder wall revealed increased wall thickness (>0.23 cm) in 83.33% cases with normal echogenicity in 50% cases.  These findings underscores the importance of urinalysis along with clinical and USG examination of dogs with UTI.
Keywords: Dogs; Incidence; Urinary tract infection; Ultrasonography